Is rodent-borne Ljungan virus responsible for mortality in migrating Norwegian lemmings (Lemmus lemmus)? - Hauffe, Heidi C.; Fevola, Cristina; Rossi, Chiara; Rizzoli, Annapaola; Niemimaa, Jukka; Henttonen, Heikki
2015